Torefaksi Pelet Tandan Kosong Kelapa Sawit Menggunakan Reaktor Putar - Purnomo, Cahyo Eko; Haryanto, Agus; Wisnu, Febryan Kusuma; Telaumbanua, Mareli (abe.fp.unila.ac.id, 2022)
Biomass is organic material produced from the process of photosynthesis. Biomass can be produced directly as a product or waste from processing agricultural or plantation products. One of the most abundant biomass is the waste generated from oil palm processing, including oil palm empty fruit bunches (OPEFB). Basically, OPEFB waste is only used as natural mulch or only disposed of in oil palm plantations. There are very few processing methods that convert into uniform shape and size biomass pellets, biomass pellets require an additional process called torrefaction, this is done to make bioenergy utilization more optimal. The quality of biomass pellets can be improved through torrefaction, which is a heat treatment process at a temperature range of 200°C–300°C under limited oxygen conditions. This study aims to examine the effect of torrefaction on the characteristics of OPEFB pellets. Pellet torrefaction uses a rotary reactor tube, a device that performs torrefaction with a tube that rotates 360º on a support shaft with the help of a transformer. Torrefaction temperatures applied were 220°C, 240°C, and 260°C with 15, 25, and 35 minutes. Pellet testing includes changes in chemical composition. The results showed that the water content of the pellets decreased from 10.57% to 1.64%. The water absorption test also showed that the torrefaction pellets were more resistant to water, so it would be very beneficial when the pellets were stored in humid conditions. Torrefaction causes a decrease in cellulose content, hemicellulose, and an increase in lignin content. Torrefaction with reactor tubes can improve the quality of EPEFB pellets and increase the added value of the product.